Red : hilang gemilang - Nur Afiqah Mohd Khalid (2019)
This paper aims to explore and reimagine the lives of actors and actresses following the end of the golden age of Malay Cinema in Singapore through an online interactive medium. This will be done through a mix of theoretical and practical components. The theoretical research will investigate the history of local Singaporean cinema in the 1950s and 1960s, and the life of P.Ramlee from the 1940s till his death in 1973 through documentaries and literature.